Generation Alpha's Impulsive Engagement with Spirituality on Social Media Platforms - Fauziah, Arinal Haq; Thelma, Chanda Chansa (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2024)
This research examines the phenomenon of Generation Alpha's consumption of religious content through social media at the Madura State Islamic Institute. The main focus of the research is to explore how Generation Alpha accesses and consumes religious information through social media platforms such as TikTok, Instagram, and YouTube and to identify the challenges regarding the validity of the information. This research uses a qualitative method with a case study approach and in-depth interviews as data collection techniques. Data sources were obtained from IAIN Madura students who represent Generation Alpha and actively use social media for religious purposes. Data analysis was conducted by adapting data reduction, display, and verification techniques to find patterns and central themes in consuming religious information. The results show that Generation Alpha is more likely to consume religious content impulsively, prioritizing ease of access and attractive formats, such as short videos and infographics, without checking the authenticity of the source. Although social media provides convenience in obtaining information, the findings also reveal that the lack of information verification can lead to misunderstanding religious teachings. This study implies the need for a better educational approach to religious digital literacy to educate Generation Alpha in critically filtering information and prioritizing valid sources such as the Qur'an and Hadith. This research provides new insights for developing more effective and accurate digital-based religious learning.